2011
DOI: 10.1002/adfm.201001756
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Conductive Coatings on Cotton, Paper, and Synthetic Fibers: Conductivity Analysis and Functional Chemical Sensing Using “All‐Fiber” Capacitors

Abstract: Conductive coatings on complex fibrous systems are attracting interest for new electronic and other functional systems. Obtaining a quantitative conductivity value for complex surface coatings is often difficult. This work describes a procedure to quantify the effective electrical conductivity of conductive coatings on non‐conductive fibrous networks. By applying a normal force orthogonal to the current and field direction, fiber/fiber contact is improved and consistent conductance values can be measured. Nylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
123
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 45 publications
3
123
0
Order By: Relevance
“…Recently, atomic layer deposition (ALD) technique has been explored to produce conformal and very thin inorganic coatings on fibrous systems such as cotton, 26,27 cellulose-based filter paper, 27−30 nonwovens, 26 synthetic 27,29 and natural fibers 31 and nanofibrillated cellulose 32 as well. ALD, which is a special type of low-temperature chemical vapor deposition, proceeds though the sequential pulses of two or more precursors separated by purging/evacuation periods.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, atomic layer deposition (ALD) technique has been explored to produce conformal and very thin inorganic coatings on fibrous systems such as cotton, 26,27 cellulose-based filter paper, 27−30 nonwovens, 26 synthetic 27,29 and natural fibers 31 and nanofibrillated cellulose 32 as well. ALD, which is a special type of low-temperature chemical vapor deposition, proceeds though the sequential pulses of two or more precursors separated by purging/evacuation periods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33−35 ALD process provides flexibility so that very thin conformal layers of metals, metal oxides or metal nitrides can be coated onto different types of three-dimensional substrates. 33−35 ALD was mostly studied on inorganic substrates, yet, recent studies showed that polymeric films 36 and complex surfaces such as fibers and nonwovens [26][27][28][29][30][31][32]36 can also be coated by ALD. It has also been shown that electrospun nanofibers can be used as a template for producing hollow nanofibers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalysts examined here were fabricated via a renounced and industrially applicable combination [10,11,18,28,29,[39][40][41], viz. electrospinning [42][43][44] and atomic layer deposition (ALD) [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…[20] The ALD of ZnO and Al-doped ZnO on cotton and nylon nonwoven fiber mats has already been investigated in the context of fabricating conductive coatings for sensor applications. [21,22] While ZnO is known to be a promising TE material for remarkably high operating temperatures (about 1000 °C), [23] the relatively high thermal conductivity of bulk ZnO results in rather poor TE efficiency at low temperatures. However, the thermal conductivity of ZnO can be decreased by nanostructuring, which results in high scattering of the heat-carrying phonons while the electronic conductivity still remains at a reasonable level.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%